Adolescent Leisure-Time Physical Activity Types and Adult Mental Disorders - Kelcie Miller; Brooklyn J. Fraser; Seana L. Gall; Kristy Sanderson; Terence Dwyer; Alison Venn; Verity Cleland (Journal of Physical Activity and Health, 2026)
Background : Adolescent leisure-time physical activity has been linked to favorable mental health outcomes in adulthood; however, the role of specific activity types remains unclear. This study aimed to determine if adolescent engagement in specific leisure-time physical activity types is associated with adult mental disorders. Methods : Data were obtained from the Childhood Determinants of Adult Health (CDAH) cohort; a 34-year Australian longitudinal study. Leisure-time physical activity at ages 15–19 years was assessed at CDAH-1 (ages 26–36 y) using the Historical Leisure Activity Questionnaire. Activities were classified into 16 groupings and further categorized as team or individual. Mood and anxiety disorders, as defined by the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition , were assessed at CDAH-1, CDAH-2 (ages 31–41 y), and CDAH-3 (ages 36–49 y) using the World Health Organization Composite International Diagnostic Interview. Participants with reported onset of a mood/anxiety disorder before age 15 were excluded to minimize reverse causation. Results : Among 2150 participants, adolescent team-based activities were associated with a lower risk of adult mood or anxiety disorders particularly in females. Activity-specific analyses indicated that participation in ball and hoop activities in females, and football and surf sports in males, were associated with a lower risk of adult mood or anxiety disorders. In contrast, cycling in females was associated with an increased risk of mood disorders. Conclusions : Adolescent participation in particular leisure-time physical activities was associated with a lower risk of adult mental disorders, with differences observed by sex. These findings contribute to evidence that early engagement in physical activity may support long-term mental well-being.